Normalized solutions to a non-variational Schrödinger system - Clapp, Mónica; Szulkin, Andrzej (Topological Methods in Nonlinear Analysis, 2023)
We establish the existence of positive normalized (in the $L^2$ sense) solutions to non-variational weakly coupled elliptic systems of $\ell$ equations. We consider couplings of both cooperative and competitive type. We show the problem can be formulated as an operator equation on the product of $\ell$ $L^2$-spheres and apply a degree-theoretical argument on this product to obtain existence.